Orientação, arquitetura e construção dos ninhos de Synoeca surinama (L) (Hymenoptera; Vespidae) () - Castellón, Eloy Guilhermo (Acta Amazonica, 1980)
The overall aspects which were covered about Synoeca surinama (L): the "habitat" of the species, preferences shown in its choice of the angle of orientation and the angle of inclination of the substrate as a means of protection; the nests construction following charcteristic patterns the model and expansion of the base cells; the standarzation in the construction, measurements and form of the involucre, beginning with walls of the most peripheral base cells, which for a bow the external border; the opening of the circular approach which is the reference point in the finalization of the involucre up to its closing. Furthermore, it is included: material used in hive construction and the architecture of the hive as defense strategy against predation and parasitism and the brood protection.